Insulin-like growth factor I and the development of colorectal neoplasia in acromegaly. - Jenkins, P; Frajese, V; Jones, A; Camacho-Hubner, C; Lowe, D; Fairclough, P; Chew, S; Grossman, AB; Monson, J; Besser, G (2000)
Patients with acromegaly are at increased risk of colorectal neoplasia and, by analogy with high-risk nonacromegalic patients, may require regular colonoscopic screening. However, it is unknown whether the risk is equal in all patients or whether some should be regarded as carrying a particularly high risk. The aims of this study were: 1) to establish the natural history of colorectal neoplasia in acromegaly; 2) to establish which patients are at increased risk of developing neoplasia; and 3) to elucidate the influence of insulin-like growth factor I (IGF-I) in adenoma formation. A prospective colonoscopic evaluation of the development of new premalignant adenomas in the colon was performed in 66 patients with biochemically proven acromegaly who had previously undergone colonoscopic screening and removal of all visible polyps. Twenty-five patients (38%) had a total of 37 polyps detected at the second colonoscopy: nine (14%) had at least one adenoma, and 18 (27%) had one or more hyperplastic polyps (2 patients had both). The development of new adenomas, but not hyperplastic polyps, was associated both with elevated serum IGF-I (P < 0.005) and, to a lesser extent, with a previous adenoma at the original colonoscopy (P < 0.07). In summary, patients with acromegaly and in whom serum IGF-I remains elevated and/or who have had a previous adenoma should be regarded as having an especially high risk for the development of subsequent colorectal neoplasia. Serum IGF-I seems to be implicated in the development of colorectal neoplasia in acromegaly, although the exact mechanisms remain uncertain.